LEGAL STUDY OF RELIGIOUS COURT’S AUTHORITY IN THE REJECTION OF ITSBAT MARRIAGE AND LEGAL CONSEQUENCES ON CHILDREN IN RELIGIOUS COURT - Anisa, Yuniar; Bakrie, Jurais Abi; Yumarni, Ani (Jurnal Sosial Humaniora, 2022)
Marriage registration aims to create order in society and also confirms the legal position of husband and wife. Meanwhile, almost every year there is always an underhand marriage whose marriage isbat is requested at the Religious Court. Itsbat is carried out by the perpetrators with different motives and reasons. According to the fatwa of the Indonesian Ulema Council Number 10 of 2008 concerning Underhand Marriage or commonly referred to as unregistered marriage, it is considered not to comply with the provisions of the legislation and often has a negative impact (madharat) on the wife and/or children they give birth to in relation to their rights. such as livelihood, inheritance rights and so on. Therefore, it is necessary to grant an itsbat for unregistered marriages, but not all marriage attributions can be granted by a judge in the Religious Courts. Based on the results of research from library and field data, the results obtained, that the Panel of Judges of the Bogor Religious Court in granting itsbat marriage, was carried out carefully and used the precautionary principle that still adhered to the principles of the Religious Courts. Meanwhile, the civil status of the child in several legal considerations is charged with legal responsibility to the parents of the child as long as the child’s civil status can be accounted for. In some other legal considerations, the civil status of the child follows the civil status of the mother/wife.